Pengaruh Kalsium Karbonat (CaCO3) Sebagai Bahan Substitusi Semen pada Beton Mutu Tinggi - Nobertus Rombe Seru; Jonie Tanijaya; Lisa Febriani (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
The main constituent of cement is calcium carbonate. In concrete mixing, a materiaI that can be used as a substitute for partial cement is calcium carbonate. The purpose of this study is to determine the compressive strength, spIit tensiIe strength, and flexural strength of concrete using calcium carbonate as a substitute for partial cement in high quality concrete. The research methodology started from examining the characteristics of the aggregate, calcium carbonate, and mix design (SNI 03-2834-200), manufacturing of cylinder and beam specimens. The results show that the composition of the concrete mixture using calcium carbonate as a cement substitution indicates that the higher the percentage of variation in calcium carbonate will reduce the quality value of the concrete.